PENGARUH METODE MEMBACA BERULANG (REPEATED READING) TERHADAP KELANCARAN DAN PEMAHAMAN MEMBACA TEKS NARASI PADA SISWA KELAS III SD - Ahmad Ilham Asmaryadi; Salahuddin, Amar; Wandari, Rasti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low reading fluency and comprehension levels of third-grade elementary school students when reading narrative texts. This situation is caused by a lack of structured and repetitive reading practice, resulting in students’ reading skills not developing optimally. One approach that can be taken to improve these skills is through the application of the repeated reading method. This study aims to determine whether the repeated reading method has an effect on the reading fluency and comprehension of narrative texts among third-grade elementary school students. This study employed a quantitative approach using an experimental method, specifically a Pre-Experimental One-Group Pretest-Posttest Design, with a sample of 13 third-grade students from UPT SD Negeri 03 Koto Baru selected using the saturation sampling technique. Data were collected through reading fluency and reading comprehension tests, then analyzed using the Shapiro-Wilk normality test and the Paired Sample t-test for hypothesis testing. The results of the study show that students’ average reading comprehension scores increased from 57.69 on the pretest to 86.92 on the posttest, while their average reading fluency scores increased from 4.46 to 7.15. The normality test results indicated that the data were normally distributed, and the Paired Sample t-Test yielded a calculated t-value of -9.296 with a significance level of 0.000 (<0.05), meaning that the null hypothesis (Ho) was rejected and the alternative hypothesis (H) was accepted. Based on these results, it can be concluded that the application of the repeated reading method has a significant effect on improving the reading fluency and comprehension of narrative texts among third-grade elementary school students; therefore, this method can serve as an effective alternative for teaching reading in elementary schools.